THE CULTURE OF “EWUH PAKEWUH” AND THE PROFESSIONALISM OF CIVIL SERVANTS UNDER BUREAUCRATIC REFORM PROGRAM IN JOKO WIDODO’S ERA: A CASE STUDY OF THE MINISTRY OF TRANSPORTATION’S ORGANIZATIONAL CULTURE - Arkandra, Daffarel -; -, Yuwanto -; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
During Joko Widodo's administration, bureaucratic reform was prioritized to improve public services and government efficiency. Among the changes implemented, the work culture of ewuh pakewuh—a Javanese concept reflecting respect and deference to superiors—has significantly impacted the professionalism of civil servants. This study analyzes the manifestations of the ewuh pakewuh culture within the Ministry of Transportation's bureaucracy, focusing on its practices, and effects on organizational performance and integrity. Using a qualitative descriptive approach, the research draws on insights from staff in the Ministry's Human Resources and Organization Bureau conducted by interviews. Findings indicate that the practice of ewuh pakewuh is viewed positively by employees, who see it as a necessary cultural norm that maintains respectful relationships with superiors. However, this ingrained practice can lead to delays in decision-making processes. In the context of Joko Widodo's bureaucratic reform, which emphasizes professionalism and structured leadership, ewuh pakewuh presents a complex challenge. While it helps sustain harmonious working relationships and organizational commitment, it may also undermine efficiency by fostering hierarchical dependency and slowing down administrative processes